Multiple endpoint in vitro toxicity assessment of a prototype heated tobacco product indicates substantially reduced effects compared to those of combustible cigarette. (February 2023) - Chapman, Fiona; Sticken, Edgar Trelles; Wieczorek, Roman; Pour, Sarah Jean; Dethloff, Ole; Budde, Jessica; Rudd, Kathryn; Mason, Elizabeth; Czekala, Lukasz; Yu, Fan; Simms, Liam; Nahde, Thomas; et al.
Abstract: This study aimed to compare the aerosol chemistry and in vitro toxicological profiles of two prototype Heated Tobacco Product (p-HTP) variants to the 1R6F Reference Cigarette. In the neutral red uptake screen the p-HTPs were 37–39-fold less potent than 1R6F, in the micronucleus assay, responses to the p-HTPs were 8–22-fold less, and in the Ames test mutagenicity was weak or removed compared to 1R6F. The cardiovascular scratch wound assay revealed 58-fold greater wound healing impairment following exposure to 1R6F smoke extracts than the p-HTPs. Furthermore, in seven cell stress-related high content screening endpoints (cell count, cytochrome c release, mitochondrial membrane potential, GSH depletion, NFkB translocation, phosphorylation of c-jun and phosphorylation of H2AX), at 4 and 24 h, responses were substantially greater to 1R6F smoke extracts at comparable nicotine levels. The reduced in vitro effects of the p-HTPs were attributed to substantial reductions (90–97%) in selected HPHCs measured compared to in 1R6F smoke. The multiple endpoint in vitro assessment approach provides greater mechanistic insight and the first reported toxicological characterisation of these p-HTPs in the literature. Overall, the findings contribute to the growing weight of evidence that HTPs may offer a reduced harm mode of nicotine delivery to adult smokers. Highlights: Prototype heated tobacco product (p-HTP) aerosols and 1R6F cigarette smoke were compared. Substantially reduced levels of harmful and potentially harmful constituents in p-HTP aerosols. Outcomes in five in vitro assays were assessed. Substantially reduced effects observed in vitro following p-HTP aerosol exposure compared to 1R6F. Findings contribute to weight of evidence for HTP tobacco harm reduction potential.